2021
DOI: 10.1055/s-0041-1732488
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Microscopy, Coproantigen Serology, and Nested Multiplex PCR in the Laboratory Diagnosis of Entamoeba histolytica Infection

Abstract: Objectives Amoebiasis is caused by the most common intestinal protozoan parasite Entamoeba histolytica. This parasite causes amoebic colitis, which is manifested by diarrhea, followed by dysentery. The laboratory diagnosis of intestinal amoebiasis in most cases is by microscopic examination of stool samples. Other nonroutine methods include coproantigen enzyme-linked immunosorbent assay (ELISA) from stool samples, serum ELISA for antibodies, stool culture, isoenzyme analysis, and polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
3
1
2
Order By: Relevance
“…As it is obvious, out of 220 stool specimen the rate of microscopy positive samples was 42.27%, this result is in line with a study conducted by Uslu H, et.al., in Malaysia who reported the presence of E. histolytica/dispar at a rate of 31.1% of in stool specimen examined with trichrome staining (10) . However, our result is in conflict with Das S, et.al research who reported the presence of E. histolytica/dispar in stool samples diagnosed with variable techniques and found that microscopy positive samples represented only 3.17% of tested patients (11) . It also differs from a study conducted in Malaysia by Ngui et.al, that found microscopy positive amoebic form in 17.6%, as well as, Previous research has also revealed a high frequency of Entamoeba infection, in rural communities ranging from 9.4% to 21.0% (12) .…”
Section: Discussioncontrasting
confidence: 99%
“…As it is obvious, out of 220 stool specimen the rate of microscopy positive samples was 42.27%, this result is in line with a study conducted by Uslu H, et.al., in Malaysia who reported the presence of E. histolytica/dispar at a rate of 31.1% of in stool specimen examined with trichrome staining (10) . However, our result is in conflict with Das S, et.al research who reported the presence of E. histolytica/dispar in stool samples diagnosed with variable techniques and found that microscopy positive samples represented only 3.17% of tested patients (11) . It also differs from a study conducted in Malaysia by Ngui et.al, that found microscopy positive amoebic form in 17.6%, as well as, Previous research has also revealed a high frequency of Entamoeba infection, in rural communities ranging from 9.4% to 21.0% (12) .…”
Section: Discussioncontrasting
confidence: 99%
“…Globally known small-size disease-causing protozoan parasites include Plasmodium spp ranging from 1 to 20 μm in size depend on their stage [36], Entamoeba histolytica usually measure range 10 to 15 µm (cyst form) and 20 to 30 µm (cyst form) [37], Giardia lamblia whose trophozoites resemble a pear or teardrop and measure 10-20 μm in length, 5-15 μm in width and 1-2 μm thickness [38], Microsporidia spp. whose resistant spore usually measure 1-4 µm [39], Cryptosporodium parvum with its oocysts are measure 4 to 6 µm in diameter [40], Trichomonas vaginalis with averages 26 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) µm in total length, with 9.5 (7.4-11.4) µm of body length and 6.8 (5.3-7.7) µm of width [41], Toxoplasma spp whose bradyzoites are 7 × 1.5μm [42], Trypanosoma spp whose length is about 25 μm in length for T. brucei [43], Babesia spp with an average size of 4,5 × 2 μm [44], Leishmania spp whose amastigotes appear round in shape and 2-4 μm in diameter while cultured promastigotes range between 15 and 25 μm in length and are ellipsoid to slender in shape [45], Cyclospora cayetanensis which oocyst very consistent in shape (round or slightly flattened on one side) and size range only between 8-10 µM [46] and Blastocystis hominis which size varies from 6 to 40 μm [47].…”
Section: Application Of Immersion Oil In Parasitology Microscopic Ana...mentioning
confidence: 99%
“…These is due to the overlap of morphological characteristics between amoeba species in addition to the limited vitality of trophozoites in diarrheal specimens and irregular fecal cyst excretion in asymptomatic hosts (Santos et al, 2011;Soares et al, 2019). Molecular approaches based on parasite DNA amplification are a very sensitive and specific tool for detecting various Entamoeba species (Santos et al, 2011;Das et al, 2021). This study was conducted to provide an update on the current status of Entamoeba species distribution among a cohort of Egyptians using multiplex PCR (mPCR) assay.…”
Section: Introductionmentioning
confidence: 99%